If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7z + 4 + 9z = 18 Reorder the terms: 4 + -7z + 9z = 18 Combine like terms: -7z + 9z = 2z 4 + 2z = 18 Solving 4 + 2z = 18 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2z = 18 + -4 Combine like terms: 4 + -4 = 0 0 + 2z = 18 + -4 2z = 18 + -4 Combine like terms: 18 + -4 = 14 2z = 14 Divide each side by '2'. z = 7 Simplifying z = 7
| 86-7x=29x+22 | | 8(-3b+8)=208 | | 7-8x=89-22x | | 162-2x=43x+17 | | -3=4+y | | -8+3(1+7r)=163 | | a^2=-12-7a | | 5x-9y=10 | | y-5=-1 | | 12-10x=60-31x | | 3c(8c+5)=0 | | 96-2x=3x+21 | | 50+(3x-4)=2(3x-4)+26 | | 10n-40n= | | 8(-8-4k)-7=-103 | | 2(d+4)=10 | | 10x+12=2x+188 | | 10x+12=2+188 | | (x+5)*3=x+41 | | (v+5)(v-18)=0 | | -4x+5y=-22 | | 7x+6+5x+3=3x-9 | | (9)y-6(y)= | | 56-4x=9-10x | | s/6+3=11 | | 143-4x=6x+13 | | 5(8-3p)=100 | | (8x-3)(2x^2-4x+4)=0 | | x=ay+b | | 5k^2+37k-24=0 | | 9yx-6yx= | | m^2+13m+12=0 |